Analisis Pengaruh Adopsi Extensible Bisnis Reporting Language (XBRL) terhadap Kinerja Perusahaan di Indonesia - Wardani, Deni; Sanita , Nurminda Ayu (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2024)
This study aims to empirically examine the effect of XBRL adoption on company and market performance in companies in Indonesia. The use of XBRL-based financial reports is expected to increase the transparency of information in financial reports so as to improve company performance and company market performance, because financial reports are one of the information-providing tools that can be used by investors in selecting issuers as investment areas. XBRL adoption is measured by a dummy variable with a value of 1 for companies that use XBRL and a value of 0 for companies that do not use XBRL, financial performance is measured using Return Of Assets, which is division between earnings before interest and tax (EBIT) and the company's average total assets, and Market performance is measured using MB, which is the ratio that compares the market value to the book value of a company's shares. This study tested 240 of 39 samples of companies listed on the Indonesian Stock Exchange's Kompas 100 Index during 2009-2020. Each independent variable is tested against the dependent variable to produce two hypotheses. Hypothesis testing was carried out using the panel data regression method with the common effect approach. The results showed that XBRL adoption had a significant effect on Return of Assets, while Market to Book had no significant effect on companies in the BEI Kompas 100 Index for the 2012-2017 period.